1981
DOI: 10.1128/mmbr.45.2.316-354.1981
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of isoprenoid quinone structural types in bacteria and their taxonomic implication.

Abstract: Each major peak is underlined. inf, Point of inflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
428
2
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,055 publications
(446 citation statements)
references
References 98 publications
(209 reference statements)
15
428
2
1
Order By: Relevance
“…The quinone analysis demonstrates that microorganisms containing Q-8, Q-9 and Q-10 were the major constituents of the microbiota at the early stage of acclimation, whereas those with partially hydrogenated menaquinones became predominant at the fully acclimated stage. According to the available information on microbial quinone systems (Collins and Jones, 1981;Yokota et al, 1992;Hiraishi, 1999b), the three major species of ubiquinones detected are possibly derived from Alphaproteobacteria, Betaproteobacteria and Gammaproteobacteria. Some portions of the Q-9 and Q-10 contents in addition to Q-10(H 2 ) might be originated from yeasts and fungi (Kuraishi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quinone analysis demonstrates that microorganisms containing Q-8, Q-9 and Q-10 were the major constituents of the microbiota at the early stage of acclimation, whereas those with partially hydrogenated menaquinones became predominant at the fully acclimated stage. According to the available information on microbial quinone systems (Collins and Jones, 1981;Yokota et al, 1992;Hiraishi, 1999b), the three major species of ubiquinones detected are possibly derived from Alphaproteobacteria, Betaproteobacteria and Gammaproteobacteria. Some portions of the Q-9 and Q-10 contents in addition to Q-10(H 2 ) might be originated from yeasts and fungi (Kuraishi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Reactor A and 8 week-operated reactor B produced similar quinone patterns to each other profiled by high proportions of partially saturated menaquinones with MK-8(H 2 ) predominating. Considering the content of higher menaquinone homologues ( n ≥ 8) and partially saturated menaquinones, which have been shown to occur mainly in Actinobacteria (Collins and Jones, 1981;Hiraishi, 1999b), members of this phylogenetic group appeared to constitute at least 60% of the total population in the fully acclimated reactors.…”
Section: Quinone Profilesmentioning
confidence: 99%
“…Chemotaxonomic studies have demonstrated that the major component of quinone differs among the various bacterial lineages. 5 This nature enables us to estimate the specific bacterial sources of the quinone homologs in environments. Quinone components in the marine sediments and possible quinone sources are summarized in Table 1.…”
Section: Quinone Compositionsmentioning
confidence: 99%
“…This menaquinone is thus probably the physiological electron acceptor for F,,,,H, oxidation in the membrane fraction of A. jufgidus. Yagi et al (1988) reported the isolation of two Feperate membrane-bound NADH :quinone oxidoreductases from the thermophilic (eu)bacterium Thermus thermophilus strain HB-8, an organism containing only menaquinone (Collins and Jones, 1981). NADH dehydrogenase I, considered to represent an energy coupling site (Meinhardt et al, 1990), is composed of at least ten different polypeptides which contain 10-12 mol non-heme iron, 10-12 mol acid-labile sulfur and 1 mol non-covalently bound FMN.…”
Section: Discussionmentioning
confidence: 99%